Penggunaan Amilum sebagai Pelapis Anti Korosi pada Baja Karbon dalam Lingkungan Asam Klorida 0,5 M - Muhammad Salahuddin; Irwan Irwan; Cut Aja Rahmawati (Jurnal Teknologi, 2022)
The purpose of this paper was to determine the affect of amylum concentration and immersion time on the corrosion rate. Amylum is used as an anticorrosive coating on carbon steel in 0,5 M hydrochloric acid  environment. Amylum concentration and immersion time affect the corrosion rate. The longer immersion time, the corrosion rate increases while the higher the concentration, the corrosion rate decreases. The highest corrosion rate was obtained at 3.58 mpy while the lowest corrosion rate was 1.24 mpy, Corrosion rates in metals can be prevented by the coating method